2014
DOI: 10.1111/eea.12257
|View full text |Cite
|
Sign up to set email alerts
|

Sampling procedures and adult sex ratios in spruce budworm

Abstract: Unbiased estimates of sex ratios that reflect local abundance of adult insects are practically difficult to obtain because many gender‐specific behavioural adaptations differentially influence the catchability of males and females in commonly applied sampling procedures. Historic data on outbreak populations of spruce budworm, Choristoneura fumiferana Clemens (Lepidoptera: Tortricidae), the major pest of conifers in Nearctic boreal forests, include dozens of sex ratio observations for 10 different sampling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…For example, the extreme variation in sex ratio observed between Agrilus spp. on detection traps is likely not due to variations in abundance of males and females in field populations but rather reflects systematic biases linked with different sampling procedures (Rhainds & Heard, 2015). In strict terms of detection (presence-absence data), however, the traps that captured the highest numbers of Agrilus (purple traps baited with cubeb oil for A. viridis, green traps for A. olivicolor and A. convexicollis) are most likely to detect potentially invasive species early in the invasion process (Allison & Redak, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the extreme variation in sex ratio observed between Agrilus spp. on detection traps is likely not due to variations in abundance of males and females in field populations but rather reflects systematic biases linked with different sampling procedures (Rhainds & Heard, 2015). In strict terms of detection (presence-absence data), however, the traps that captured the highest numbers of Agrilus (purple traps baited with cubeb oil for A. viridis, green traps for A. olivicolor and A. convexicollis) are most likely to detect potentially invasive species early in the invasion process (Allison & Redak, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While thinning appeared to interact with gout to influence sex ratio, its effect was extremely subtle: we could detect no treatment effects on sex ratio when unthinned and thinned stands were analyzed separately, and all sex ratios were close to 1:1 (as expected for resident budworm populations; Rhainds and Heard, 2015). Thinning did interact with both budworm density and gout to influence budworm survivorship: survivorship declined with budworm density and with gout in unthinned stands, but not (significantly) in thinned ones.…”
Section: Thinningmentioning
confidence: 73%
“…Unbiased estimates of sex ratios for local populations are difficult to obtain because of gender‐specific behavioural differences that influence trap catch data. Sex ratios from multiple different sampling procedures were not markedly different from 1 : 1 (Miller, ; Rhainds & Heard, ; but see Graham, ), therefore, if we assume that approximately half our surviving population were females, we can infer fecundity. It has previously been shown that the potential fecundity of females from spruce trees increased by an average of 69 eggs for each 1‐mm increase in fore wing length (Thomas et al ., ).…”
Section: Discussionmentioning
confidence: 94%